A Symbols of the Human Life Journey in the Poetry Collection Sesanti Tedhak Siti by Iman Budi Santosa: A Symbols of the Human Life Journey in the Poetry Collection Sesanti Tedhak Siti by Iman Budi Santosa - Utik Aulia Nur Fajriah; Yusro Edy Nugroho; RM. Teguh Supriyanto (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This study examines the symbols and meanings of Javanese traditional mythology in the poetry anthology Sesanti Tedhak Siti by Iman Budi Santosa. This poetry anthology contains the journey of human life from the first step on earth to the end of life. The purpose of this study is to reveal Javanese traditional mythology in the form of symbols and meanings found in the poetry collection Sesanti Tedhak Siti by Iman Budi Santosa. Therefore, this article discusses the forms of 1) denotative symbols and meanings, 2) connotative symbols and meanings, and 3) mythical symbols and meanings in the poetry collection Sesanti Tedhak Siti. The research method used an objective approach. The theory used was Roland Barthes' semiotics. The data consisted of expressions that were suspected to be Javanese mythological symbols. The data source is the poetry anthology Sesanti Tedhak Siti by Iman Budi Santosa. The data was obtained through heuristic and hermeneutic reading. Based on the analysis results, denotation, connotation, and myth were found. These findings symbolize the phases of human life, starting from stepping on the ground, adulthood, family life, old age, and death.